Response of the functional traits of Schoenoplectus tabernaemontani to simulated warming in the Napahai wetland of northwestern Yunnan, China - Liu, Zhenya; Zhao, Yiqing; Yu, Hongyan; Zhao, Yao; Guo, Huijun; Sun, Mei (Frontiers in Ecology and Evolution, 2024)
The impact of climate warming on wetland ecosystems is a current focal point in ecological research. In this study, the Napahai wetland, a typical plateau wetland in northwest Yunnan Province, was selected as the study site to understand the growth and survival strategies of emergent plants in a plateau wetland under climate warming conditions. Open-top chambers (OTCs) were used to simulate warming in three treatments (i.e., control group, 2.0 ± 0.5°C, and 4.0 ± 0.5°C) in order to study the responses of the functional traits of the dominant emergent plant Schoenoplectus tabernaemontani to simulated warming. The results showed that simulated warming significantly reduced the photosynthetic carbon assimilation capacity and biomass accumulation of S. tabernaemontani, as well as its nitrogen content and vascular bundle density, while it significantly increased the vascular bundle size. The growing season accumulated temperature (AT) and the mean temperature of the hottest month (WT) were the main temperature factors influencing the functional traits of S. tabernaemontani. In summary, simulated warming significantly affected the functional traits of S. tabernaemontani, which demonstrated effective adaptation to warming conditions. As the temperature rises and the light and productivity decrease, S. tabernaemontani prioritizes the supply of limited resources to the underground part to ensure the biomass supply of the reproductive structure. This study provides a case for revealing the response patterns and ecological adaptation strategies of plateau wetland plants to climate warming.